An EZ-Diffusion Model Analysis of Attentional Ability in Patients With Retinal Pigmentosa - Luo, Yan-Lin; Wang, Yuan-Ying; Zhu, Su-Fang; Zhao, Li; Yin, Yan-Ling; Geng, Meng-Wen; Lei, Chu-Qi; Yang, Yan-Hui; Li, Jun-Fa; Ni, Guo-Xin (Frontiers in Neuroscience, 2021)
Retinitis pigmentosa (RP) is characterized by visual acuity decrease, visual fields loss. However, it remains unknown about the impact of visual field loss on the cognitive performance of RP patients. In the present study, in order to understand whether and how RP affects spatial processing and attentional function, one spatial processing task and three attentional tasks were conducted on RP patients and healthy controls. In addition, an EZ-diffusion model was performed for further data analysis with 4 parameters, mean decision time, non-decision time, drift rate, and boundary separation. It was found that in the spatial processing task, compared with the control group, RP group exhibited a slower response speed in large and medium visual eccentricity, and slower drift rate for the large stimulus, which is strongly verified by the significant linear correlation between the visual field eccentricity with both reaction time (p = 0.047) and non-decision time (p = 0.043) in RP patients. In the attentional orienting task and the attentional switching task, RP exerted a reduction of speed and an increase of non-decision time on every condition, with a decrease of drift rate in orienting task and boundary separation in switching task. In addition, the switching cost for large stimulus was observed in the control group, but not in the RP group. The stop-signal task demonstrated similar inhibition function between two groups. These findings implied that RP exerted the impairment of spatial cognition correlated with the visual field eccentricity, mainly in the peripheral visual field. Moreover, specific to the peripheral visual field, RP patients had deficits in the attentional orienting and flexibility, but not in the attentional inhibition.